DC–DC converter design with ferrite core inductor for implantable neurostimulation device compatible with MRI. Issue 15 (1st July 2016) - Bai, Bing; Jiang, Changqing; Zhang, Feng; Li, Luming
Abstract : DC–DC converting circuit with ferrite core inductor has many advantages in circuit design of implantable neurostimulation devices such as deep brain stimulation device. However, it may be problematic under MRI because of the saturation of the ferrite core of the inductor which would lead to dramatic decline of inductance. To address this issue, the influence of the ferrite core inductor saturation on the circuit functionality of the stimulator is systematically analysed. It was revealed that under proper conditions, it was possible to maintain the normal stimulation output even if the ferrite core saturated. The results were validated by simulation and experiment and the circuit design criteria were derived.